2007
DOI: 10.1111/j.1540-8175.2007.00443.x
|View full text |Cite
|
Sign up to set email alerts
|

Severe Tricuspid Regurgitation Due to Entrapment of the Anterior Leaflet of the Valve by a Permanent Pacemaker Lead: Role of Real Time Three‐Dimensional Echocardiography

Abstract: Pacemaker leads may impair tricuspid valve coaptation and they are a well-known cause of mild tricuspid regurgitation. Occasionally, right ventricular leads worsen tricuspid regurgitation over time and patients develop late-onset symptoms of right-sided heart failure. The exact mechanism of this clinical entity is rarely identifiable by 2D-echocardiography only. This case report details a patient with severe tricuspid regurgitation secondary to immobilization of the anterior leaflet of the tricuspid valve by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 12 publications
1
23
0
2
Order By: Relevance
“…Mechanisms that have been reported previously include obstruction to leaflet closing, perforation, and laceration. [1][2][3][4][5]12,13 Lin et al 7 found that PPM-related tricuspid malfunctions were caused by various mechanisms; the largest subset of patients (39%) had lead impingement only of the tricuspid valve leaflets at surgery, but other mechanisms included adhesion of the PPM or ICD lead to a tricuspid valve leaflet (34%), leaflet perforation (17%), and entanglement of the tricuspid valve apparatus (10%). On that basis, insufficient valve closure may be the main cause of PPM-lead-related TR, as shown by our data.…”
Section: Mechanism Of Lead-related Trmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanisms that have been reported previously include obstruction to leaflet closing, perforation, and laceration. [1][2][3][4][5]12,13 Lin et al 7 found that PPM-related tricuspid malfunctions were caused by various mechanisms; the largest subset of patients (39%) had lead impingement only of the tricuspid valve leaflets at surgery, but other mechanisms included adhesion of the PPM or ICD lead to a tricuspid valve leaflet (34%), leaflet perforation (17%), and entanglement of the tricuspid valve apparatus (10%). On that basis, insufficient valve closure may be the main cause of PPM-lead-related TR, as shown by our data.…”
Section: Mechanism Of Lead-related Trmentioning
confidence: 99%
“…7 The 3-dimensional echocardiography (3-DE) has been recently developed for assessing tricuspid valve morphology and pathology, including TR, [8][9][10][11] and case reports on its utility in the diagnosis of PPM-and ICD-lead-related TR have been published. 12,13 However, the ability of 3-DE to identify both the anatomical lead route through the tricuspid valve and lead-induced valve malfunction has not been studied systematically. …”
mentioning
confidence: 99%
“…Так, в исследовании G. Lin et al перфорация створки электродом или ее повреждение на обычной трансторакальной 2D-эхокардиографии были выявлены лишь у 12% пациентов [10]. Для более детальной оценки по-ложения электрода и состояния клапанного ап-парата используется трансторакальная 3D-эхо-кардиография [11].…”
Section: имплантация антиаритмических устройств является методом выбоunclassified
“…экстракций электродов [34]. Экс-тракция хронически имплантированных элект-родов является комплексным, малотравматич-ным и высокоэффективным методом лечения в крупных и высокоспециализированных цент-рах, но может сопровождаться фатальными осложнениями [11]. Необходимо отметить, что количество осложнений при данном виде мани-пуляций из года в год становится меньше и со-ставляет примерно 0,4-1% [33].…”
Section: имплантация антиаритмических устройств является методом выбоunclassified
“…The en face view of the TV may assist in the diagnosis of TV variants such as the presence of a bileaflet TV which has only been described using 3D-TTE [54]. 3D echocardiography can be helpful in identifying whether pacemaker or intracardiac defibrillator leads contribute to tricuspid regurgitation [55]. Further, 3D color flow Doppler showed that the TV VC is more of an elliptic shape compared to the MV [56].…”
Section: Tricuspid and Pulmonic Valvesmentioning
confidence: 99%